Cognitive Scaffolding Through Discovery Learning: A Mixed-Methods Study on Disaster Risk Reduction Pedagogy and Its Impact on Metacognitive Skills in Secondary Education - Audy Bintang Tantular; Tuti Mutia; Alice Sabrina Ismail (Future Space: Studies in Geo-Education, 2025)
Geography learning in class has problems, one of which is the low level of students' high-level thinking abilities as happened in class XI-8. Based on observations, the problem lies in students' passivity in the learning process, therefore a model is needed that is able to attract students' interest. The pre-cycle test results showed an average score of 67 which is relatively low. It is necessary to apply appropriate and effective learning models to be used in classroom learning, namely the discovery learning learning model. The aim of this research is to find out whether applying the discovery learning model in disaster mitigation learning can improve students' high-level thinking abilities. This type of research is Classroom Action Research (CAR) and is carried out in two cycles. Each cycle consists of four stages, namely planning, acting, observing, reflecting. The subjects of this research were 35 students in class XI-8 of SMAN 1 Kepanjen. Data collection uses 4 test questions that refer to indicators of high-level thinking abilities. Data analysis uses quantitative descriptive. The results show that from pre-cycle to cycle one there was an increase in high-level thinking skills by 16% with a mean of 78 and in cycle two there was an increase of 17% with a mean of 91. It can be concluded that the application of the discovery learning model syntax can improve high-level thinking skills student.